A novel variation in DEPDC5 causing familial focal epilepsy with variable foci - Wang, Yanchi; Niu, Wenbin; Shi, Hao; Bao, Xiao; Liu, Yidong; Lu, Manman; Sun, Yingpu (Frontiers in Genetics, 2024)
DEPDC5 (DEP domain containing protein 5) is a component of GATOR1(GAP activity towards rags complex 1) protein, which is an inhibitor of the amino acidsensing branch of the mTORC1 pathway. GATOR1 complex variations were reported to correlate with familial focal epilepsy with variable foci (FFEVF). With the widely application of whole-exome sequencing (WES), more and more variations in DEPDC5 were uncovered in FFEVF families. Here, we describe a novel variant, c.1217+2T>A, in DEPDC5 identified by WES in an FFEVF affected family. This splicing variant that occurred at the 5′ end of intron 17 was confirmed by mini-gene splicing assays, which impacted alternative splicing and led to inclusion of an intron fragment. Analysis of the transcribed mRNA sequence indicates that the translation of the protein is terminated prematurely, which is very likely to result in loss-of-function of the protein and lead to the occurrence of FFEVF. In conclusion, the results suggest c.1217+2T>A variation in DEPDC5 might be the genetic etiology for FFEVF in this pedigree. This finding expands the genotype spectrum of FFEVF and provided new etiologic information for FFEVF.